Syn City. - Fairley, P.
It is said that China is one of the fastest-growing electricity economies. Thanks to the local high-sulfur coal fueling its growth, it also has some of the country's dirtiest air. However, high-sulfur coal is choking Shandong's residents and stunting crops, it has also inspired a creative application of coal gasification technology that could help clean up China's air and quench its thirst for electricity. This paper shows how Zaozhuang's hybrid chemical and power plant could help clean up China's energy sector. It is Zaozhuang's use of syngas that is truly unique, by simultaneously producing a chemical and a considerable amount of electricity
Keywords: Zaozhuang hybrid chemical plant; Carbon dioxide emission reduction; Coal gasification technology; Electricity economies; High-sulfur coal fueling; Polygen technology; Power plant